Analysis of Influencing Factors and Noise Reduction Effects of Viaduct Noise in City Rail Transit - WANG Chaoliang; QIU Haihui (Chengshi guidao jiaotong yanjiu)
［Objective］ It is aimed to provide advice for viaduct noise control in city rail transit and application of noise reduction measures. ［Method］ Based on theories of vehicle-track dynamics, wheel-rail vibration radiation, and viaduct structure vibration radiation, a prediction model for viaduct noise in city rail transit is established. The influence of factors such as train speed, distance from viaduct structure, viaduct type, and noise barriers on city rail transit viaduct noise is analyzed. ［Result & Conclusion］ When train speed exceeds 100 km/h, the viaduct noise increases by 1.8-5.5 dB(A) compared to train speeds below 100km/h. For single-cell single-box girders, single-cell double-box girders, and U-shaped girders, the peak frequency range of viaduct noise is 50-80 Hz, with a peak frequency at 63 Hz. At a distance of 7.5 m from the track centerline, the single-cell double-box girder demonstrates the lowest noise levels at all heights, whereas noise levels at the girder sides of single-cell single-box girders and U-shaped girders are higher by 1.0-4.1 dB(A) and 5.2-10.6 dB(A), respectively, compared to single-cell double-box girders. Near-track noise barriers with heights of 0.90 m or more above the track surface ensure a noise reduction effect of 7.0 dB(A) at 500 Hz frequency band, with noticeable noise reduction effects maintained across frequencies above 630 Hz.